Investigating how Agile Software Practitioners Repay Technical Debt in Software Projects - Soares, Gabriel; Freire, Sávio; Rios, Nicolli; Pérez, Boris; Castellanos, Camilo; Correal, Darío; Mendonça, Manoel; Izurieta, Clemente; Seaman, Carolyn; Spínola, Rodrigo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
Context: The adoption of agile methodologies can bring benefits to software projects, but such methodologies are also prone to technical debt (TD) accumulation. Knowing the practices used for repaying debt items and practice avoidance reasons (PARs) considered for explaining their non-repayment can aid agile practitioners to improve their capacity to manage TD. Aims: To investigate how agile software practitioners repay TD items in software projects. Method: We analyze a data set composed of 179 answers collected through a globally distributed family of industrial surveys on TD. Results: Agile practitioners tend to not repay debt items, mainly for those items that happen very often. The main PARs that explain the non-repayment are focusing on short-term goals, lack of organizational interest, and cost. Conversely, the repayment practices code refactoring, investing effort on TD repayment activities, and investing effort on testing activities are the more commonly used practices for eliminating debt items. We organize all this information in TD repayment boards. Conclusion: TD repayment in agile software projects is still far from ideal. The set of practices and PARs, and the boards can support practitioners in sharing their experiences in TD repayment.